Changing dietary practices in phenylketonuria - Macdonald, Anita; Gökmen-Ozel, Hülya; Daly, Anne (The Turkish Journal of Pediatrics, 2009)
In recent years, there has been much focus on research on non-dietary treatments in phenylketonuria (PKU). However, diet is likely to remain the major treatment for many years to come, since it has continued to be developed and consistent improvements have occurred. For example, with protein substitute, studies have tried to define the optimal dose and timing of intake; changes in palatability and presentation appear to have led to the long-term maintenance of acceptable blood phenylalanine control in teenage patients, and the low phenylalanine protein source glycomacropeptide is being considered as an alternative source to non-phenylalanine amino acids. Some countries are now adopting a simpler approach to dietary management, allowing a wider range of lower low phenylalanine foods without measurement, in combination with controlled phenylalanine exchange systems. Patients with PKU who are partially responsive to sapropterin dihydrochloride still require some dietary treatment. Long-term studies are required for examining the combined use of sapropterin dihydrochloride and diet to determine its impact on nutritional adequacy, growth, and blood phenylalanine variability. Generally, whether diet is used alone or in combination with sapropterin dihydrochloride, its true impact on quality of life and lifestyle should be investigated. Overall, it is likely we will continue to see many changes in the dietary treatment in the next five years, and hopefully this will lead to a better outcome for patients.